Accounts of Family Conflict in Home Hospice Care: The Central Role of Autonomy for Informal Caregiver Resilience. (May 2019) - Benson, Jacquelyn J.; Parker Oliver, Debra; Demiris, George; Washington, Karla
End-of-life caregiving is a highly stressful experience often fraught with conflict and tension. However, little is known about the ways family conflict manifests for informal caregivers of home hospice patients (IHCs). Framed by relational dialectics theory, the purpose of this study was to provide nurses and other health care professionals with an empirical understanding of how IHCs experience family conflict and tensions associated with caregiving. A second aim was to determine what strategies IHCs use to manage these family conflicts. Data used in this qualitative secondary analysis were originally collected as part of a randomized clinical trial of an IHC support intervention. Based on thematic analysis of data from 25 IHCs who reported family conflict, a conceptual model of caregiver resilience was developed from the themes and categories that emerged during the coding stage. Autonomy was identified as a central tension. IHCs used several strategies to address family conflict including communication, formal support, and emotional self-care.